Successive construction method for substrate material and self-smoothing mortar

The continuous construction method addresses prolonged construction times and adhesion issues by using precise moisture removal, surface treatment, and timely application of self-smoothing mortar, achieving high adhesion strength and smoothness.

JP2025007909AActive Publication Date: 2025-01-17TAIHEIYO MATERIALS CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023109633
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-17
Estimated Expiration
2043-07-03

AI Technical Summary

Technical Problem

Existing construction methods for self-smoothing mortar on concrete floors are prolonged due to reliance on environmental conditions and lack sufficient adhesion strength, leading to potential peeling issues.

Method used

A continuous construction method involving moisture removal, surface roughening, and precise timing of self-smoothing mortar application based on penetration values, using specific mortar compositions and standards to ensure high adhesion strength and smoothness.

Benefits of technology

Enables construction management independent of environmental conditions, shortens construction time, and ensures high adhesion strength and smoothness between the base material and self-smoothing mortar.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007909000001
    Figure 2025007909000001
  • Figure 2025007909000002
    Figure 2025007909000002
  • Figure 2025007909000003
    Figure 2025007909000003
Patent Text Reader

Abstract

To provide a successive construction method for substrate material and self-smoothing mortar that can manage construction and shorten the period of the construction regardless of construction environment conditions, while also ensuring high adhesion strength between the substrate material and a self-smoothing mortar hardened body.SOLUTION: A successive construction method for substrate material and self-smoothing mortar comprises the following steps in this order: a water removing step of removing bleeding water produced from a substrate material if a penetration value measured at a construction site with a substrate material cast through an N type penetration test of the substrate material is 1 to 40 mm; a surface processing step of roughening the entire surface of the substrate material after the water removing step; and a mortar casting step of constructing the self-smoothing mortar, wherein a flow value measured at the construction site after the surface processing step is 230 to 290 mm based upon the Japanese Architectural Standard Specification (quality standard of self-leveling material) JASS 15M-103:2019, and a flow-down time of a J10 funnel is 10 to 30 seconds based upon the Japan Society of Civil Engineers standard (flowability test method for PC grout) JSCE-F531:2018.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a base material and a method for continuous application of self-smoothing mortar. [Background technology]

[0002] The floors of concrete buildings have poor surface accuracy when the concrete is simply poured, and a reliably horizontal surface is not formed.

[0003] When it is desired to ensure smoothness after concrete is poured, it is common to pour self-smoothing mortar (self-leveling material). Self-smoothing mortar is a slurry-like mixture made by adding water to a mixture of various admixtures, with cement and fine aggregate as the base material, and using the high fluidity characteristic of this slurry to form a smooth floor surface.

[0004] The current self-leveling method involves pouring self-smoothing mortar onto the surface of an already-constructed concrete base. In other words, it is common to use the self-leveling material at least two weeks after the concrete has been poured.

[0005] Therefore, although smoothness can be ensured by pouring self-smoothing mortar into the base concrete, the construction period becomes longer, which is a problem. Also, if the adhesive strength at the interface between the base concrete and the hardened self-smoothing mortar is not sufficiently ensured, there is a risk of peeling due to impact, etc. Therefore, a construction method that can be constructed in a short period of time, ensures smoothness, and obtains high adhesive strength is required.

[0006] For example, Patent Document 1 discloses a construction method in which a self-leveling material is poured within 2 to 10 hours after a base concrete is poured. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 7-113314 Summary of the Invention [Problem to be solved by the invention]

[0008] However, although this method can shorten the construction period, the setting time of the base concrete may vary due to its mix and the influence of environmental conditions such as temperature and humidity. If the self-leveling material is poured when the condition of the base concrete is not constant, the adhesion between the base concrete and the self-leveling material may be impaired.

[0009] Although smoothness can be ensured by pouring self-smoothing mortar into the base concrete, the increased number of processes results in a longer construction period. Also, if the adhesive strength at the interface between the base concrete and the hardened self-smoothing mortar is not sufficiently ensured, there is a risk of peeling due to impact, etc. Therefore, a construction method that can be constructed in a short period of time, ensures smoothness, and provides high adhesive strength is required.

[0010] Therefore, an object of the present invention is to provide a continuous construction method for a base material and self-smoothing mortar, which allows construction management and shortens the construction period regardless of construction environmental conditions, and in which the base material and the self-smoothing mortar hardened body have high adhesive strength. [Means for solving the problem]

[0011] As a result of thorough investigation into the above-mentioned problems, the inventors discovered that it is possible to apply a continuous base material and self-smoothing mortar by determining the appropriate timing for applying the self-smoothing mortar based on the penetration value from an N-type penetration test after applying the base material, and then pouring a specific self-smoothing mortar.

[0012] That is, the present invention is as follows. [1] A method for continuous construction of a base material and self-smoothing mortar, comprising the steps of: a moisture removal process for removing bleeding water generated from the base material when the base material is poured and the penetration value of the base material in an N-type penetration test is 1 to 40 mm when measured at the construction site; a surface treatment process for roughening the entire surface of the base material after the moisture removal process; and a mortar pouring process for pouring self-smoothing mortar having a flow value of 230 to 290 mm as specified in the Architectural Institute of Japan standard "Quality Standard for Self-Leveling Materials" JASS 15M-103:2019 when measured at the construction site and a J10 funnel flow time of 10 to 30 seconds as measured in accordance with the Japan Society of Civil Engineers standard "Draft Method for Fluidity Test of PC Grout" JSCE-F531:2018, in the order mentioned. [2] The continuous construction method described in [1], wherein the surface treatment process is brushing and / or removal of the fragile layer. [3] A continuous construction method as described in [1] or [2], in which the roughening in the surface treatment process is dense. [4] The continuous construction method according to [1] or [2], wherein the self-smoothing mortar contains cement, a water-reducing agent, a thickening agent, fine aggregate and water. [5] The continuous construction method according to [4], further comprising an expansive material and / or gypsum. [6] The continuous construction method described in [4], wherein the water reducing agent is a polycarboxylic acid-based water reducing agent. [7] The continuous application method described in [4], wherein the thickener is a cellulose-based thickener. [8] The continuous construction method according to [4], wherein the water content is 60 to 100 parts by mass per 100 parts by mass of cement. Effect of the Invention

[0013] According to the present invention, it is possible to provide a continuous construction method for a base material and self-smoothing mortar, which allows construction management and shortens the construction period regardless of the construction environmental conditions, and in which the base material and the self-smoothing mortar hardened body have high adhesive strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, one embodiment of the present invention will be described in detail.

[0015] In the continuous application method of the base material and self-smoothing mortar of this embodiment, when the base material is poured and measured at the application site, the penetration value of the base material by the N-type penetration test is 1 to 40 mm. A moisture removal process is performed to remove bleeding water generated from the base material, a surface treatment process is performed to roughen the entire surface of the base material after the moisture removal process, and a mortar pouring process is performed to apply a self-smoothing mortar having a flow value of 230 to 290 mm as specified in the Architectural Institute of Japan standard "Quality Standard for Self-Leveling Materials" JASS 15M-103:2019 in a 20 ° C environment and a flow time of 10 to 30 seconds in a J10 funnel as measured in accordance with the Japan Society of Civil Engineers standard "PC Grout Fluidity Test Method (Draft)" JSCE-F531:2018.

[0016] (Base material application process) The base material is not particularly limited, and ordinary concrete, mortar, etc. can be used.

[0017] In an embodiment of the present invention, after the construction of the base material, when the penetration value by the N-type penetration test is 1 to 40 mm when measured at the construction site, the moisture removal process and the surface treatment process are performed. If the penetration value by the N-type penetration test is outside the above range, the base material and the self-smoothing mortar do not integrate, and the adhesion strength decreases. From the viewpoint that the base material is easily roughened and the base material and the self-smoothing mortar hardened body are integrated to further improve adhesion, the penetration value by the N-type penetration test of 1 to 40 mm is more preferably 5 to 35 mm, and even more preferably 10 to 30 mm. In this specification, the "penetration value by the N-type penetration test" refers to the penetration depth when a rod used in JIS A 1101:2020 "Concrete Slump Test Method" is dropped from a height of 750 mm. By measuring the penetration value by the N-type penetration test at the construction site, construction management can be performed more accurately than the elapsed time from casting, which changes depending on the temperature.

[0018] (moisture removal process) After checking the condition of the base material by the penetration value by the above-mentioned N-type penetration test, the bleeding water generated from the base material is removed. By removing the bleeding water, the self-smoothing mortar becomes less likely to separate into materials. There is no particular limitation on the means for removing the bleeding water, and a rag, sponge, etc. can be used.

[0019] (Surface treatment process) After the moisture removal step, the entire surface of the base material is roughened. Roughening refers to making the surface of the base material finely uneven. The unevenness refers to a state in which a relatively flat base material is provided with lines, scratches, pinholes, or other depressions caused by brushing with a broom or brush. The means for roughening is not particularly limited, and examples include brushing with a broom, brush, or dragonfly, and removal of a fragile layer using a polisher. Roughening is performed on the entire surface of the base material, and it is preferable that the density of the unevenness is dense. 2 This refers to a state in which there is at least one scratch within a 1cm 2 Preferably, there are 5 or more projections and recesses in the surface, more preferably 10 or more projections and recesses, and even more preferably 15 or more projections and recesses. The width of the projections and recesses is not particularly limited, but is preferably 0.1 mm or more, and more preferably 0.5 mm or more and 3.0 mm or less. The depth of the projections and recesses is also not particularly limited, but is preferably 0.2 mm or more, and more preferably 0.5 mm or more and 4.0 mm or less. Roughening the surface strengthens the adhesion between the base material and the hardened self-smoothing mortar, and the denser the roughening, the stronger the adhesion tends to be. To roughen the surface densely, methods include brushing the entire surface with a broom or brush that has dense tips, removing the brittle layer on the entire surface with a polisher, or repeatedly roughening the entire surface.

[0020] (Mortar pouring process) After the surface treatment step, the self-smoothing mortar is poured. The thickness of the self-smoothing mortar layer when hardened is preferably 1 to 50 mm, more preferably 1.5 to 40 mm, and even more preferably 2 to 30 mm. If the thickness of the hardened self-smoothing mortar is within the above range, it is easy to ensure smoothness and the durability tends to be excellent.

[0021] The self-smoothing mortar has a flow value of 230 to 290 mm as specified in the Architectural Institute of Japan standard "Quality Standard for Self-Leveling Materials" JASS 15M-103:2019. If the flow value of the self-smoothing mortar is outside the above range, the material is likely to separate, and the surface appearance of the self-smoothing mortar after hardening is not excellent. From the viewpoint of being more excellent in self-leveling and being easy to apply without material separation even when applying the self-smoothing mortar to an unfinished base material, the flow value of the self-smoothing mortar is preferably 240 to 280 mm, more preferably 250 to 275 mm.

[0022] The self-smoothing mortar has a flow time of 10 to 30 seconds using a J10 funnel, measured in accordance with the Japan Society of Civil Engineers standard "PC Grout Fluidity Test Method (Draft)" JSCE-F531:2018. If the flow time of the self-smoothing mortar is outside the above range, the application of the self-smoothing mortar takes a long time, adhesion to the base material becomes insufficient, and the aesthetic appearance of the surface after the self-smoothing mortar hardens is also not good. The flow time of the self-smoothing mortar is preferably 12 to 25 seconds, more preferably 14 to 20 seconds. The flow value and flow time of the self-smoothing mortar are preferably measured at the application site before the mortar is poured. By having the properties of the self-smoothing mortar at the application site within the above ranges, continuous application can be controlled regardless of the environmental temperature.

[0023] The self-smoothing mortar is not particularly limited as long as it is a material having self-leveling properties. Examples of the self-smoothing mortar include those containing cement, a water reducing agent, a thickening agent, fine aggregate, and water.

[0024] Various types of cement can be used, including, for example, various Portland cements such as ordinary, early strength, extra early strength, low heat and moderate heat, ecocement, rapid hardening cement, fly ash cement, etc. One type of cement may be used alone, or two or more types may be used in combination.

[0025] The content of cement is preferably 20 to 45 parts by mass, more preferably 25 to 40 parts by mass, and even more preferably 27 to 38 parts by mass, relative to 100 parts by mass of the powder component of the self-smoothing mortar. If the content of cement is within the above range, it is easy to ensure sufficient fluidity and various strength expression properties as a self-leveling material. The powder component refers to the entire powder constituting the self-smoothing mortar, including aggregates such as fine aggregates.

[0026] The water reducing agent includes a high-performance water reducing agent, a high-performance AE water reducing agent, an AE water reducing agent, and a superplasticizer. Examples of such water reducing agents include those specified in JIS A 6204:2011 "Chemical admixtures for concrete". Examples of the water reducing agent include polycarboxylic acid water reducing agents, naphthalene sulfonic acid water reducing agents, lignin sulfonic acid water reducing agents, and melamine water reducing agents. Among these, polycarboxylic acid water reducing agents are preferred. The water reducing agents may be used alone or in combination of two or more types.

[0027] The content of the water reducing agent is preferably 0.1 to 5 parts by mass, more preferably 0.3 to 3 parts by mass, and most preferably 0.4 to 1.5 parts by mass, in terms of solid content, relative to 100 parts by mass of cement. If the content of the water reducing agent is within the above range, better fluidity is easily obtained when the mortar is made, and the compressive strength is also easily improved.

[0028] The type of thickener is not particularly limited, and examples thereof include cellulose-based thickeners, acrylic thickeners, and guar gum thickeners. As the thickener, cellulose-based thickeners are preferred. As the cellulose-based thickener, examples thereof include methylcellulose-based thickeners such as carboxymethylcellulose, methylcellulose, and hydroxypropylmethylcellulose, hydroxyethylcellulose, and hydroxypropylcellulose. The thickener may be used alone or in combination of two or more.

[0029] The content of the thickener is preferably 0.01 to 1 part by mass, more preferably 0.03 to 0.8 parts by mass, and even more preferably 0.05 to 0.5 parts by mass, calculated as solid content relative to 100 parts by mass of cement. If the content of the thickener is within the above range, it is easy to exhibit an appropriate effect of suppressing aggregate separation.

[0030] Examples of fine aggregate include river sand, silica sand, crushed sand, kansui stone, limestone sand, slag aggregate, etc. Among these, it is preferable to use aggregate such as silica sand or limestone adjusted to a grain size that does not contain fine powder or coarse aggregate as the fine aggregate. One type of fine aggregate may be used alone, or two or more types may be used in combination. It is preferable to use fine aggregate with a grain size of 1.2 mm or less (passing through a 1.2 mm sieve), which is commonly used.

[0031] The particle size of the fine aggregate is not particularly limited, and can be adjusted within the required particle size range of the fine aggregate. The particle size of the fine aggregate can be considered from the coarse particle ratio defined by JIS A 1102:2014 "Sieving test method for aggregates". From the viewpoint of easily obtaining better fluidity and easily suppressing bleeding, the coarse particle ratio of the fine aggregate is preferably 1 to 3, more preferably 1.5 to 2.8, and even more preferably 1.8 to 2.4.

[0032] The content of the fine aggregate is preferably 100 to 300 parts by mass, more preferably 120 to 250 parts by mass, and even more preferably 140 to 200 parts by mass, relative to 100 parts by mass of cement. If the content of the fine aggregate is within the above range, it is easy to ensure sufficient fluidity and compressive strength as a self-leveling material.

[0033] The water content is preferably 60 to 100 parts by mass, more preferably 65 to 95 parts by mass, and even more preferably 70 to 90 parts by mass, relative to 100 parts by mass of cement. When the amount of water is within the above range, good fluidity is easily obtained.

[0034] Various admixtures (materials) may be blended into the self-smoothing mortar as long as the effects of the present invention are not impaired. Examples of the admixtures (materials) include expansion agents, antifoaming agents, waterproofing agents, rust inhibitors, shrinkage reducing agents, water retention agents, pigments, water repellents, and efflorescence inhibitors.

[0035] The preparation of the self-smoothing mortar can be carried out using a kneading tool similar to that used for general mortar, etc., and is not particularly limited. Examples of the kneading tool include a mortar mixer, a hand mixer, a tilting mixer, and a twin-shaft mixer.

[0036] In the continuous construction process of this embodiment, the steps from pouring the base material to pouring the self-smoothing mortar are performed continuously, so that the time for the base material to harden can be omitted, thereby shortening the construction period and reducing costs. In addition, the continuous construction integrates the base material and the self-smoothing mortar, improving their adhesion strength. In the continuous construction according to this embodiment, the primer coating process that is usually required when pouring the self-smoothing mortar is not necessary, and not only can the construction period be shortened and costs be reduced, but the generation of bubbles after pouring the self-smoothing mortar, which is thought to be caused by the primer, can also be reduced. Therefore, the continuous construction method of this embodiment can be suitably used for short-term construction or construction in situations where high durability is required. EXAMPLES

[0037] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples. Tests and evaluation tests were carried out in an environment of 20°C.

[0038] [material] Cement [C]: Ordinary Portland cement Gypsum (G): anhydrous gypsum, Blaine specific surface area: 7100 cm 2 / g Expansive material (EX): Lime-based expansive material Thickener [MC]: Water-soluble cellulose ether (viscosity of 2% by weight aqueous solution at 20°C: 4820 mPa s) Water reducing agent [AD]: Polycarboxylic acid-based high-performance water reducing agent Fine aggregate (S): Mixed sand made by mixing No. 6, No. 7, and No. 9 silica sand to adjust the coarse aggregate ratio to 0.15 to 0.5.

[0039] [Self-smoothing mortar mix] The materials were mixed according to the ratio shown in Table 1, and mixed using a high-speed hand mixer (1000 rpm) while being poured into a pail containing a pre-measured amount of mixing water. After the materials were poured in, the mixture was mixed for 1 minute to prepare a self-smoothing mortar. The self-smoothing mortar was mixed immediately before starting pouring.

[0040] [Table 1]

[0041] [Continuous application method of base material and self-smoothing mortar] The continuous application method of the base material and the self-smoothing mortar was carried out according to the following procedure. [1] Mixing and pouring of base materials Concrete with a mix of 21-15-20N (nominal strength - slump - maximum dimension of coarse aggregate) was poured into a wooden formwork (dimensions 450mm x 600mm) fitted with reinforcing bars (D10 deformed steel bars) to a thickness of 100mm, and then tapped and the surface was smoothed using a trowel and wooden ruler. [2] Moisture removal process The bleeding water generated from the base material was collected from the surface layer of the base material and absorbed with a rag, sponge, etc. to remove the moisture. [3] Surface treatment process After the moisture removal process, the entire surface of the base material was roughened with a brush (fine knots were made on the front side). The unevenness created by the roughening process was 1 cm 2 There were 10 to 20 of them inside, each measuring 0.2 to 3.0 mm wide and 0.5 to 3.0 mm deep. [4] Mortar casting process After the surface treatment process, a self-smoothing mortar with a flow value of 230-290 mm as specified in the Architectural Institute of Japan standard "Quality Standard for Self-Leveling Materials" JASS 15M-103:2019 and a J10 funnel flow time of 10-30 seconds as measured in accordance with the Japan Society of Civil Engineers standard "PC Grout Fluidity Test Method (Draft)" JSCE-F531:2018 was poured to a thickness of 10 mm on the base material. Some reference products (self-smoothing mortars E, F, G) were poured using mortar whose flow value or J10 funnel flow time did not meet the above-mentioned values. [2] to [4] were carried out at the following times (points) when the penetration value of the base material in the N-type penetration test was measured. The penetration value in the N-type penetration test was measured by dropping the rod used in JIS A 1101:2020 "Slump Test Method for Concrete" from a height of 750 mm. Timing 1: Penetration value by N-type penetration test: 70 mm Timing 2: Penetration value by N-type penetration test: 33 mm Timing 3: Penetration value by N-type penetration test: 20 mm Timing 4: Penetration value by N-type penetration test: 9mm

[0042] [Evaluation method] [Method for evaluating fresh properties of self-smoothing mortar] Fluidity (flow test, flow down test) The flow value was measured according to JASS-15M-103:2019 (quality standard for self-leveling materials) of the Architectural Institute of Japan. The flow time was measured using a J10 funnel tester in accordance with the Japan Society of Civil Engineers standard "Test method for flowability of PC grout (draft)" JSCE-F531:2018. ·Material separation resistance Immediately after mixing, a hand was placed into the container containing the mortar to check whether or not the fine aggregate had settled to the bottom of the container. If no settlement was observed, it was marked as "no," and if settlement was observed, it was marked as "yes." The measurements were carried out at an ambient temperature of 20°C immediately after mixing the self-smoothing mortar.

[0043] [Method of evaluating mortar after successive application of base material and self-smoothing mortar] ·Self-smoothing mortar surface aesthetics Fourteen days after the mortar was poured, the surface of the hardened self-smoothing mortar was visually inspected, and those with almost no cracks, lifting, or bubbles, or those with only minor cracks or bubbles that did not affect the finishing treatment, were rated as ◯, and those with many cracks or bubbles were rated as ×. -Adhesive strength with the base material In accordance with JASS-15M-103:2019 (quality standard for self-leveling materials) of the Architectural Institute of Japan, the adhesive strength was measured 14 days after the mortar was poured. The evaluation standard was 0.7N / mm 2 The test was carried out using the "Construction Research Institute type adhesive strength tester using a hydraulic jack." -Fracture surface with base material After the adhesive strength test with the base material was conducted, the fracture surface was visually inspected. Those in which 80% or more of the cross section was fractured in the base concrete layer were marked with an ◯, and those in other cases were marked with an ×.

[0044] The self-smoothing mortar used, the construction procedure, construction timing, and various evaluation results are shown in Tables 2 and 3.

[0045] [Table 2]

[0046] [Table 3]

[0047] It was confirmed that the construction method of the Example had excellent adhesive strength with the base material and good surface appearance by using a high-flow self-smoothing mortar with material separation resistance and by carrying out a moisture removal and surface treatment process for the base concrete. On the other hand, the construction method of the Comparative Example had weak adhesive strength and did not have a good surface appearance.

Claims

1. When the base material is poured and measured at the construction site, the penetration value of the base material by the N-type penetration test is 1 to 40 mm. A moisture removal process for removing bleeding water generated from the base material; a surface treatment step of roughening the entire surface of the base material after the moisture removal step; a mortar pouring step of pouring a self-smoothing mortar having a flow value of 230 to 290 mm as defined in the Architectural Institute of Japan standard "Quality Standard for Self-Leveling Materials" JASS 15M-103:2019 when measured at the construction site after the surface treatment step, and a J10 funnel flow time of 10 to 30 seconds as measured in accordance with the Japan Society of Civil Engineers standard "Draft Method for Testing Fluidity of PC Grout" JSCE-F531:2018, in the order given.

2. The continuous application method according to claim 1 , wherein the surface treatment step is brushing and / or removal of a brittle layer.

3. The continuous construction method according to claim 1 or 2, wherein the roughening in the surface treatment step is dense.

4. The continuous construction method according to claim 1 or 2, wherein the self-smoothing mortar comprises cement, a water reducing agent, a viscosity improver, fine aggregate and water.

5. The continuous construction method according to claim 4, further comprising an expansive material and / or gypsum.

6. The continuous construction method according to claim 4, wherein the water reducing agent is a polycarboxylic acid-based water reducing agent.

7. The continuous application method according to claim 4, wherein the thickener is a cellulosic thickener.

8. The continuous construction method according to claim 4, wherein the content of the water is 60 to 100 parts by mass per 100 parts by mass of the cement.

Citation Information

Patent Citations

  • Anti-static polyurethane mortar self-leveling floor and construction process thereof

    CN114278048A

  • New self-leveling construction method

    JP1995113314A

  • Cement-based self-leveling composition

    JP2000034153A

  • Management method of spraying time of concrete placing joint treatment agent

    JP2013256804A

  • High strength pourable gypsum floor underlayments and methods of providing same

    US5424099A